An Open Trial of a New Acceptance-Based Behavioral Treatment for Major Depression With Psychotic Features. (May 2013) - Gaudiano, Brandon A.; Nowlan, Kathryn; Brown, Lily A.; Epstein-Lubow, Gary; Miller, Ivan W.
Research suggests that cognitive and behavioral therapies produce significant benefits over medications alone in the treatment of severe, nonpsychotic major depression or primary psychotic disorders such as schizophrenia. However, previous research has not demonstrated the efficacy of psychotherapy for major depression with psychotic features. In this initial treatment development study, we conducted an open trial of a new behavioral intervention that combines elements of behavioral activation and acceptance and commitment therapy for depression and psychosis. Fourteen patients with major depressive disorder with psychotic features were provided with up to 6 months of Acceptance-Based Depression and Psychosis Therapy (ADAPT) in combination with pharmacotherapy. Patients reported a high degree of treatment credibility and acceptability. Results showed that patients achieved clinically significant and sustained improvements through posttreatment follow-up in depressive and psychotic symptoms, as well as psychosocial functioning. In addition, the processes targeted by the intervention (e.g., acceptance, mindfulness, values) improved significantly over the course of treatment, and changes in processes were correlated with changes in symptoms. Results suggest that ADAPT combined with pharmacotherapy is a promising treatment approach for psychotic depression that should be tested in a future randomized trial.